Efektivitas Penyuluhan Dengan Metode Simulasi Terhadap Peningkatan Pengetahuan Dan Sikap Tentang Sarapan Pada Murid Di SDN 3 Delod Peken Tabanan - Indriani, A.A. Lystia Putri; M. Kes, Ir. Desak Putu Sukraniti; M.Si, Ni Putu Agustini, SKM. (Jurnal Ilmu Gizi : Journal of Nutrition Science, 2024)
Breakfast is very important for elementary school students especially to maintain the concentration of learning and support achievement in school. Many elementary school students who ignore breakfast before going to school due to lack of knowledge about breakfast. Therefore an education is needed to increase the knowledge and attitudes of elementary school students about breakfast. The targets of this study is to determine the effectiveness of counseling with the simulation method on knowledge and attitudes about breakfast in elementary school students. This type of research is experimental quazi with a one group pretest-posttest design study design. The sampling technique uses proportional random sampling. The total population is 88 people with a total sample of 73 people. This research was conducted in January-May 2019. Instruments for collecting data using questionnaires about breakfast. The results showed that there was a change in knowledge and attitude about breakfast. Hypothesis testing using paired T-Test samples obtained p value sig. 2-tailed) knowledge of 0,000 and p value of sig. 2-tailed) breakfast attitude at 0.024. It was concluded that counseling using an effective simulation method on increasing knowledge and attitudes about breakfast for students at SDN 3 Delod Peken Tabanan. It is expected that extension officers in the school can improve and develop the provision of material on breakfast to elementary school students by using methods and media that are more interesting and in accordance with children's development such as simulation methods with the breakfast monopoly media.Keywords             : simulation, knowledge, attitude, breakfast